Epidemiological trends and clinical characteristics of human leptospirosis in Wenzhou, Zhejiang Province, China, 2020–2022 - YueYing Zhou; XianMin Wang; HuiJuan Li; Zhengxing Wu; Ning Pan; HongYe Ning; SaiDuo Liu; XinChun Ye; Chao-Chao Qiu; KaiJia Wu; JiChan Shi (Journal of Infection in Developing Countries)
Objective: To observe the clinical characteristics and epidemic trends of human leptospirosis in Wenzhou, Zhejiang Province, China, from 2020 to 2022 and to provide a scientific basis for prevention and control in this area.